2018
DOI: 10.1002/adsc.201800596
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Green Solvents Associated to Pd/C as Heterogeneous Catalyst for Direct Arylation of Heteroaromatics with Aryl Bromides

Abstract: Metal residues are certainly one of the major sources of contamination of products in metalcatalyzed direct arylation reactions. We found that the use of only 1 mol% of the heterogeneous catalyst Pd/C promotes very efficiently the direct arylations of most heteroaromatics. In the presence of this catalyst and potassium acetate as the base, the direct arylation of thiophenes, furans, pyrroles, thiazoles, imidazoles or isoxazoles, using aryl bromides as coupling partners, proceeds highly regioselectively and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 73 publications
2
27
0
1
Order By: Relevance
“…Pd/C catalyst displays several advantages over homogeneous palladium catalysts: 1) it is easy to handle because it is not sensitive to air or moisture, 2) it is readily available on a large scale and at an affordable cost, 3) it can be removed by simple filtration, 4) recycling of the recovered Pd/C residues is possible in some cases or they can be reconditioned. However, to date the Pd‐catalyzed direct arylation of heteroarenes using Pd/C is limited to the reactions with aryl halides . A few other heterogeneous Pd‐catalysts such as Pd(OH) 2 , zeolites or nanoparticles have also been successfully employed for the direct arylation of heteroaromatics with aryl halides ,…”
Section: Introductionmentioning
confidence: 99%
“…Pd/C catalyst displays several advantages over homogeneous palladium catalysts: 1) it is easy to handle because it is not sensitive to air or moisture, 2) it is readily available on a large scale and at an affordable cost, 3) it can be removed by simple filtration, 4) recycling of the recovered Pd/C residues is possible in some cases or they can be reconditioned. However, to date the Pd‐catalyzed direct arylation of heteroarenes using Pd/C is limited to the reactions with aryl halides . A few other heterogeneous Pd‐catalysts such as Pd(OH) 2 , zeolites or nanoparticles have also been successfully employed for the direct arylation of heteroaromatics with aryl halides ,…”
Section: Introductionmentioning
confidence: 99%
“…The superior catalytic performance of 2 b was again demonstrated in our preparation of 5 i', [6c,20] 5 e', [21] and 9 a, [6h,15a,19,22] which were previously prepared exclusively from the corresponding aryl bromides, not chlorides. In a literature example, 2-bromotoluene was .…”
Section: Full Papermentioning
confidence: 69%
“…Very recently, our group reported that only 1 mol% of the Pd/C catalyst promotes the direct arylations of a wide range of heteroaromatics using aryl bromides as coupling partners (Schemes , b) . With this catalyst and KOAc as the base in DMA, without additives or co‐catalysts, the direct arylation of 2‐substituted thiophenes and furans proceeded highly regioselectively at C5‐position in moderate to very high yields.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Our group also reported that with specific heteroarenes such as thiazoles, imidazo[1,2‐ a ]pyridine and imidazo[1,2‐ b ]pyridazine, these arylations with Pd/C catalyst proceeded in “green” solvents such as 3‐methylbutan‐1‐ol (Scheme ) . For example, the arylation of 2‐isopropy‐4‐methylthiazole with 4‐bromobenzonitrile in 3‐methylbutan‐1‐ol using 1 mol% of 10 % Pd/C catalyst afforded the C5‐arylated thiazole in 97 % yield.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%